2018
DOI: 10.3389/fmicb.2018.01607
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microbiota in Patients Treated by Surgery or Chemotherapy by 16S rRNA Sequencing Reveals Potential Biomarkers for Colorectal Cancer Therapy

Abstract: Colorectal cancer (CRC) is the third most diagnosed cancer worldwide due to its high difficulty in early diagnosis, high mortality rate and short life span. Recent publications have demonstrated the involvement of the commensal gut microbiota in the initiation, progression and chemoresistance of CRC. However, this microbial community has not been explored within CRC patients after anti-cancer treatments. To this end, we performed next generation sequencing-based metagenomic analysis to determine the compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 61 publications
2
87
0
1
Order By: Relevance
“…Recent research has found great alterations of gut microbiota after the removal of colorectal carcinoma in favor of a more normal microbiota . Moreover, reduced microbial diversity has been reported among CRC patients treated with surgery, while few alterations occur because of the adenoma resection, which is similar to our finding. The reason might be that the impact of carcinoma on the intestinal environment is much greater than adenoma, thus reflecting their corresponding impact on the microbiota.…”
Section: Discussionsupporting
confidence: 90%
“…Recent research has found great alterations of gut microbiota after the removal of colorectal carcinoma in favor of a more normal microbiota . Moreover, reduced microbial diversity has been reported among CRC patients treated with surgery, while few alterations occur because of the adenoma resection, which is similar to our finding. The reason might be that the impact of carcinoma on the intestinal environment is much greater than adenoma, thus reflecting their corresponding impact on the microbiota.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, a small study (n � 11) among mixed pelvic cancer patients, using 454 high-throughput pyrosequencing, found a significant decrease in the Shannon diversity index after pelvic RT compared with before RT [14]. Interestingly, one cross-sectional study compared the fecal microbiota of 33 healthy individuals, 17 colorectal cancer (CRC) patients before treatment, 14 CRC patients treated with chemotherapy, and 5 CRC patients after surgery, but found no significant differences in alpha diversity indexes among groups [29]. Nonetheless, our study findings suggest that the global balance of bacterial populations in the gut changed in response to genotoxic stress such as CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [26] 5-Fluorouracil Fusobacterium nucleatum Nonbeneficial Induce BIRC3 expression via theTLR4/NF-κB pathway Yuan et al [27] 5-Fluorouracil Antibiotics increase Proteobacteria Nonbeneficial -Deng et al [28] Tegafur plus oxaliplatin Fusobacterium nucleatum Nonbeneficial -Geller et al [29] Gemcitabine Gammaproteobacteria Nonbeneficial Bacterial CDD inactivates gemcitabine Yu et al [30] 5 Attention has been paid to ICIs in the clinic. Immunotherapy targeting PD-1 has emerged as an effective strategy for the treatment of several cancers.…”
Section: Chemotherapymentioning
confidence: 99%
“…Distinct responses to chemotherapy and immunotherapy in cancer patients have provoked robust interest in identifying useful biomarkers to optimize patient selection and management. Fecal sample analysis using 16S rRNA sequencing has provided evidence that Fusobacterium nucleatum is related to the chemoresistance of CRC, as well as other specifically chemotherapy-associated bacterial strains [28]. This may be an optimal microbial marker candidate during anticancer treatment.…”
Section: Microbial Markers For Therapeuticsmentioning
confidence: 99%